2021
DOI: 10.3389/fmars.2021.626082
|View full text |Cite
|
Sign up to set email alerts
|

Remote Predictions of Mahi-Mahi (Coryphaena hippurus) Spawning in the Open Ocean Using Summarized Accelerometry Data

Abstract: Identifying complex behaviors such as spawning and fine-scale activity is extremely challenging in highly migratory fish species and is becoming increasingly critical knowledge for fisheries management in a warming ocean. Habitat use and migratory pathways have been extensively studied in marine animals using pop-up satellite archival tags (PSATs), but high-frequency data collected on the reproductive and swimming behaviors of marine fishes has been limited by the inability to remotely transmit these large dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 52 publications
9
31
1
Order By: Relevance
“…Results from this study generally agree with previous reported mahi distributions (see Introduction). Although fish in the present study were tested at an earlier age than wild-tagged adults, our results also tended to align with thermal ranges reported from PSAT data obtained from adult wild mahi (Schlenker et al, 2021). This, combined with the large habitat usage overlap across life stages of mahi (most time spent in surface waters), suggests that physiological performance observed in the present study may provide insight into thermal habitat utilization patterns of larger adults that are logistically difficult to test in laboratory settings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Results from this study generally agree with previous reported mahi distributions (see Introduction). Although fish in the present study were tested at an earlier age than wild-tagged adults, our results also tended to align with thermal ranges reported from PSAT data obtained from adult wild mahi (Schlenker et al, 2021). This, combined with the large habitat usage overlap across life stages of mahi (most time spent in surface waters), suggests that physiological performance observed in the present study may provide insight into thermal habitat utilization patterns of larger adults that are logistically difficult to test in laboratory settings.…”
Section: Discussionsupporting
confidence: 86%
“…Pharmacological blockade of the sarcoplasmic reticulum (SR) did not change contractile force between ∼21-26 • C, but was effective at temperatures below 20 • C, suggesting that mahi have the ability to recruit additional intracellular calcium needed for contraction at low temperatures, but are generally less reliant on the SR for contraction between ∼21-26 • C (Galli et al, 2009). Temperatures below 20 • C where SR recruitment would occur, would likely only be transient based on behavior of satellitetagged wild mahi (Merten et al, 2014b;Schlenker et al, 2021). Another recent study examining mitochondrial function in adult mahi reared close to 26 • C and assayed at 20, 26, and 30 • C, found that heart mitochondria were more sensitive when compared to those from the red muscle, and showed reduced phosphorylation efficiency as temperatures increased (Lau et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations